2009
DOI: 10.1002/net.20367
|View full text |Cite
|
Sign up to set email alerts
|

Solving a resource allocation problem in wireless mesh networks: A comparison between a CP‐based and a classical column generation

Abstract: This article presents a column generation approach to a resource allocation problem arising in managing Wireless Mesh Networks. The problem consists in routing the given demands over the network and to allocate time resource to pairs of nodes. Half-duplex constraints are taken into account together with the aggregate interference due to simultaneous transmissions, which affects the signal quality. Different problems are considered, according to the assumptions on the transmission power and rate. The resource a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…The proposed approach extends and generalizes classical optimization schemes for routing and scheduling in non-cooperative networks [30][31][32][33]. Therefore, it also has a practical value in those network scenarios where propagation and traffic conditions are quite stable and a centralized scheme can be used to optimize radio resources, like for example in wireless mesh networks.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…The proposed approach extends and generalizes classical optimization schemes for routing and scheduling in non-cooperative networks [30][31][32][33]. Therefore, it also has a practical value in those network scenarios where propagation and traffic conditions are quite stable and a centralized scheme can be used to optimize radio resources, like for example in wireless mesh networks.…”
Section: Introductionmentioning
confidence: 89%
“…It has been shown that integer programming formulations based on identifying feasible configurations admits, within a reasonable amount of computing time, an optimal or very-close-to optimal routing and scheduling solution for networks of up to moderate size [32,33].…”
Section: An Integer Programming Formulationmentioning
confidence: 99%
“…Our previous work described in Li et al (2012) develops a simulated annealing algorithm to generate a sub-optimal solution consisting of several CSs for the problem of joint link rate assignment and transmission scheduling. The papers (Björklund et al 2004;Capone et al 2010b) also treat generating compatible sets through a pricing problem in column generation for various applications in wireless networks.…”
Section: Introductionmentioning
confidence: 99%
“…Differently than in asymptotic analysis where random networks are considered [1], this problem is commonly considered in performance engineering of wireless networks with arbitrary topology and propagation coefficients [2]. Notably, a weighted version of this problem is the key subproblem in many radio resource management aspects, such as link scheduling [3], [4], where different sets of compatible parallel transmissions need to be selected, and routing [6], [7], where transmissions over multiple links are required.…”
Section: Introductionmentioning
confidence: 99%
“…[9], [10] and the references therein). Its relevance within the theory of wireless networks is related to benchmarking and performance analysis of protocols and systems, but it also has practical validity in static all-wireless networks (like Wireless Mesh Networks) where propagation conditions are almost constant and a centralized management of radio resources is applicable [7], [11].…”
Section: Introductionmentioning
confidence: 99%